Identification Of Antimalarial Compounds And Their Mode Of Actions - Mahmud, Fauze (2022)
Malaria is one of the most significant infectious diseases in the tropics, claiming around half-million lives annually, mainly due to Plasmodium falciparum (P. falciparum) infections. To date, P. falciparum has developed full or partial resistance towards all three classes of antimalarials, including against the artemisinin. Hence, it may jeopardize the efficacy of the current antimalarial treatment regimen, the Artemisinin Combination Therapy (ACT), in the near future. Therefore, there is an utmost need to identify a new antimalarial compound with a novel mode of action (MoA). This study mainly focused on identifying antimalarial compounds from soil microorganisms isolated from Malaysia and Japan. The crude extracts of these strains showed potent antimalarial activity in a preliminary assay against Pf 3D7 (wild type). The crude extracts of Malaysian strains also inhibited the activity of human GSK-3β (75 % similar to P. Falciparum GSK-3 (Pf GSK-3)).